MODELING ATMOSPHERIC O2 OVER PHANEROZOIC TIME - Berner R.A. (My University, 2001)
A carbon and sulfur isotope mass balance model has been constructed for calculating the variation of atmospheric O2 over Phanerozoic time. In order to obtain realistic O2 levels, rapid sediment recycling and O2-dependent isotope fractionation have been employed by the modelling. The dependence of isotope fractionation on O2 is based, for carbon, on the results of laboratory photosynthesis experiments and, for sulfur, on the observed relation between oxidation/reduction recycling and S-isotope fractionation during early diagenetic pyrite formation. The range of fractionations used in the modeling agree with measurements of Phanerozoic sediments by others.Results, derived from extensive sensitivity analysis, suggest that there was a positive excursion of O2 to levels as high as 35% during the Permo-Carboniferous. High O2 at this time agrees with independent modeling, based on the abundances of organic matter and pyrite in sediments, and with the occurrence of giant insects during this period. The cause of the excursion is believed to be the rise of vascular land plants and the consequent increased production of O2 by the burial in sediments of lignin-rich organic matter that was resistant to biological decomposition.
Keywords: Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная